2013
DOI: 10.1093/scan/nst123
|View full text |Cite
|
Sign up to set email alerts
|

Neural representation and clinically relevant moderators of individualised self-criticism in healthy subjects

Abstract: Many people routinely criticise themselves. While self-criticism is largely unproblematic for most individuals, depressed patients exhibit excessive self-critical thinking, which leads to strong negative affects. We used functional magnetic resonance imaging in healthy subjects (N = 20) to investigate neural correlates and possible psychological moderators of self-critical processing. Stimuli consisted of individually selected adjectives of personally negative content and were contrasted with neutral and negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 67 publications
2
28
0
Order By: Relevance
“…It is also likely there are interactions among the neural systems engaged by self-processing and emotion processing. For example, self-criticism and negative self-concept, which both characterize self-injuring youth (Claes et al, 2010a; Glassman et al, 2007), are also each linked to greater limbic activity during exposure to adjectives of personally-relevant negative content versus exposure to neutral and negative non-self-referential adjectives (Doerig et al, 2014). Overall, the extant literature reviewed here lends support for studying the hypothesis that depressed youth with NSSI may show higher activity in both CMS and limbic areas when engaged in self-processing compared to depressed youth without NSSI and healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…It is also likely there are interactions among the neural systems engaged by self-processing and emotion processing. For example, self-criticism and negative self-concept, which both characterize self-injuring youth (Claes et al, 2010a; Glassman et al, 2007), are also each linked to greater limbic activity during exposure to adjectives of personally-relevant negative content versus exposure to neutral and negative non-self-referential adjectives (Doerig et al, 2014). Overall, the extant literature reviewed here lends support for studying the hypothesis that depressed youth with NSSI may show higher activity in both CMS and limbic areas when engaged in self-processing compared to depressed youth without NSSI and healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Crucially, contrasting self-critical vs. negative non-self-referential adjectives engages activation in the medial posterior cingulate cortex [67], suggesting that this area is specifically relevant during self-related evaluation.…”
Section: Self-criticismmentioning
confidence: 99%
“…In fact, the exact network involved in positive and negative self-appraisal seems puzzling, as two studies [65,66] found the same network of regions when contrasting between self-critical vs. neutral and positive self-appraisal vs. neutral conditions. Using verbal material, dorsomedial and dorsolateral PFC [65], mid-frontal regions, insula, precuneus and visual areas [66,67] responded to both positive and negative conditions when contrasted with neutral adjectives. Positive self-appraisal seems to evoke stronger activity in the precuneus, visual areas [65], amygdala and insula [65,67] when directly contrasted with self-critical adjectives, whereas self-critical displayed increased occipital activations [65], but also amygdala activation [67].…”
Section: Self-criticismmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that, for this specific example, it was sufficient to rely on the participant's self-report, but there may be cases where researchers need to use other methods [see (5) below]. In another study by Doerig et al [31] on self-criticism, healthy participants were instructed in a pre-fMRI test to pick 6 ‘prototypes' from a list of self-critical adjectives that most personally related to them. In order to assess the subjective relevance of each of these, participants were then asked to rate them on a Likert-type scale, answering the question: ‘How negatively would you rate this characteristic of yourself?…”
Section: Guidelines For Resolving the Emotion Stimulus Critique: Potementioning
confidence: 99%